PELAKSANAAN KEGIATAN ASURANSI USAHA TERNAKSAPI DAN KERBAUDIKABUPATENROKAN HULU TAHUN 2019-2021 - Ahmad Junaidi (Universitas Pasir Pengaraian, 2022)
The Ministry of Agriculture of the Republic of Indonesia in 2021 will implement an insurance program specifically for cattle/buffaloes, this program is called Cattle/Buffalo Business Insurance (AUTS/K). This Cattle/Buffalo Business Insurance is a loss insurance scheme that covers the risk of death and loss of cattle or buffalo combined with a premium subsidy by the government for the included cattle or buffalo. The implementation of this insurance program, of course, has terms and procedures for participating in the Cattle/Buffalo Business Insurance program, therefore the author reviews and discusses the procedures for implementing the Cattle/Buffalo Business Insurance program. At this writing, the author uses a sociological juridical method (socio legal research), which is an approach to the problem by looking at the theory and legal aspects (laws) that apply to the facts and practice in the field by conducting research. The results of the research and discussion following the program Cattle/Buffalo Business Insurance are breeders who are breeding and/or breeding, female cows and buffalo, still productive at least 1 year old and maximum 8 years old, small scale breeders. The procedure is that the insured registers himself through the UPT of the Local Livestock Department of Agriculture, visitation by the Insurer PT. Asuransi Jasa Indonesia (Persero) and field officers put ear tags on the ears of cows or buffalo. The claim payment procedure is carried out within 14 working days from the date of approval of the claim by the insurer. Payment of claims by the insurer is paid directly to the account number of the insured.